Revitalisasi Amaliyah Tasawuf KH. Muslih Mranggen dalam Pendidikan Karakter Santri Era Modern - Khoir, Mulyanto Abdullah; Hidayah, Nur; Hudallah, Hudallah (Lembaga Yasin AlSys, 2025)
Amaliyah tasawuf constitutes an integral part of the Islamic spiritual tradition, playing a significant role in shaping the character and personality of santri (Islamic boarding school students). KH. Muslih Abdurrahman Mranggen, a prominent tarekat scholar and founder of Pesantren Futuhiyyah, developed a tasawuf-based education system through practices such as zikir, riyāḍah, wirid, and khalwat, which serve as instruments for spiritual development. This study aims to examine the forms of amaliyah tasawuf taught by KH. Muslih and explore their relevance to character education in the modern era. A qualitative approach was employed, using library research and interviews as the primary data collection methods. The findings reveal that KH. Muslih’s tasawuf practices contribute significantly to strengthening spiritual dimensions and fostering the character of santri, emphasizing values such as patience, sincerity, humility (tawāḍuʿ), and social responsibility. These tasawuf practices extend beyond personal piety, encouraging the internalization of moral values in the social lives of students. The study concludes that revitalizing the tasawuf-based values of KH. Muslih is highly relevant in addressing the moral degradation challenges faced by today’s youth and can serve as a foundational model for designing character education systems rooted in Islamic spirituality.